A Sensor Positioning Scheme with High Accuracy in Nonuniform Wireless Sensor Networks. (4th June 2013) - Park, Junho; Park, Hyuk; Seong, Dong-ook; Yoo, Jaesoo
In wireless sensor networks, a geographical positioning scheme is one of core technologies for sensor applications such as disaster monitoring, environment monitoring, and military services. For this reason, the research for range-free positioning schemes had progressing actively. And a density probability scheme based on the central limit theorem and normal distribution theory has been proposed to improve the location accuracy in nonuniform sensor network environments. The density probability scheme estimates 1-hop distance by using communication between nodes. After that, it estimates the final position of an unknown node. But the density probability scheme has a problem that it has equivalent 1-hop distance for all of nodes in the same area. To overcome this problem, we propose a novel sensor positioning scheme in non-uniform wireless sensor networks. As a result, the proposed scheme ensures the high accuracy of sensor positioning in non-uniform networks. To show the superiority of our proposed scheme, we compare it with the existing scheme such as DV-based position scheme. Our experimental results show that the proposed scheme improves by about 36% sensor positioning accuracy over the existing scheme on average even in non-uniform wireless sensor networks.